Natives of the BSSR in the losses of the Red Army during the liberation of north-eastern regions of Poland in 1944–1945 - Bushuev, Aleksei S. (Journal of the Belarusian State University. History, 2024)
Social characteristic of natives of the BSSR as part of the combat losses suffered by the Red Army in 1944–1945 during the liberation of the north-eastern regions of Poland from Nazi occupation is explored. The work was carried out on the basis of an analysis of a prosopographic database compiled by the author, which provides information about 330 natives of the BSSR who died during defensive and offensive battles near the borders of East Prussia and were buried in mass graves near Suwalki (today the city belongs to the Podlaskie Voivodeship of Poland). The territorial features of mobilisation are noted, the directions of the mobilisation flow of conscription resources before being sent to the front are recorded. The predominant age groups of mobilised natives of the BSSR who died near the borders of East Prussia are determined. The conclusion about the significant role of Belarusians in the liberation of Polish lands from the Nazi invaders is drawn.